Nanocellulose Aerogels for Supporting Iron Catalysts and In Situ Formation of Polyethylene Nanocomposites. (3rd February 2017) - Hees, Timo; Zhong, Fan; Rudolph, Tobias; Walther, Andreas; Mülhaupt, Rolf
Abstract : Aerogels of nanocellulose (NC) prepared by freeze‐drying of cellulose nanofibrils (CNF) hydrogels and followed by impregnation with methylaluminoxane serve as nanoporous organic supports for immobilizing single site iron catalysts such as bisiminopyridine iron(II) complexes. The resulting catalyst systems, exploiting renewable biomaterials as organic supports, are highly active in low pressure ethylene polymerization. They afford simultaneous control of high density polyethylene (HDPE) particle morphology and facile NC dispersion within the HDPE matrix. In the early stage of ethylene polymerization, mesoscopic shape replication and NC‐mediated templating yield platelets containing an NC core and a HDPE shell, as confirmed by scanning electron microscopy (SEM) of virgin polyethylene powders. Opposite to conventionally dried CNF hydrogels, forming large agglomerates, this facile NC aerogel‐mediated in situ NC/HDPE nanocomposite formation is vastly superior to melt compounding of HDPE with NC, failing to produce such fine NC dispersions. On increasing NC content to 3.0 wt%, both Young's modulus (+50%) and tensile strength (+40%) increase at the expense of elongation at break (−80%). According to the SEM analysis of NC/HDPE morphology, the dispersion of NC nanosheets together with the in situ formation of "shish‐kebab" polyethylene fiber‐like structures accounted for HDPE matrix reinforcement. Abstract : Immobilization of highly active iron‐based single‐site catalysts for ethylene polymerization on nanocellulose (NC) aerogels enables in situ NC/high density polyethylene nanocomposite formation and controlled particle growth by mesoscopic shape replication. Herein, variations of polymerization conditions and mechanical properties of the resulting materials are investigated. Interestingly, superior stiffness and strength are paralleled by the presence of oriented self‐reinforcing polyethylene nanostructures ("shish‐kebab").